“Letting the leaders pass”: barriers to using traditional ecological knowledge in comanagement as the basis of formal hunting regulations - Padilla, Elisabeth; Kofinas, Gary P. (Resilience Alliance, 2014)
We studied a case of failure in applying traditional ecological knowledge (TEK) in comanagement as the basis for formal hunting regulations. We based the study on the Porcupine Caribou (Rangifer tarandus) Herd “let the leaders pass” policy, established for the Dempster Highway of the Western Canadian Arctic, and identified conditions creating barriers in the successful application of TEK through comanagement. Stated as propositions, identified barriers include: (1) the context-specific nature of TEK limits its application in resource management regulations; (2) changes in traditional authority systems, hunting technology, and the social organization of harvesting caribou affect the effectiveness of TEK approaches in a contemporary social setting; (3) indigenous efforts toward self-government and political autonomy limit regional comanagement consensus in a heterogeneous cultural landscape; (4) the mismatch of agency enforcement of hunting regulations and TEK-based education is problematic. We analyzed the case through four historical phases of caribou management, complementing the study with a literature review of TEK and wildlife comanagement to explain why TEK integration of caribou leaders in regulatory resource management fell short of success. Identifying and understanding the social dynamics related to these barriers make apparent solutions for transforming the comanagement process.